1989
DOI: 10.1063/1.101757
|View full text |Cite
|
Sign up to set email alerts
|

Well size related limitations on maximum electroabsorption in GaAs/AlGaAs multiple quantum well structures

Abstract: Experimentally determined maximum electroabsorption in GaAs/Al0.33Ga0.67As multiple quantum wells over the quantum well width range of 17–260 Å is related to the confinement of the electronic wave functions in the quantum well, increasing with enhanced confinement. However, for very narrow wells, this increase in maximum electroabsorption is diminished by strong broadening of the excitonic resonances due to phonon scattering, eventually leading to a peak value of 22 200 cm−1 at a 35 Å well width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The first point in the width optimization of a single QW was chosen to be 11 monolayers (ML). Indeed, experimental studies of the absorption spectra for single QWs with width of 17 to 260 Å have already demonstrated that, for very narrow wells, the exciton peaks are strongly broadened due to the phonon scattering, and the well width at which the maximum peak absorption is observed is about 35 Å [23].…”
Section: Design Of Cqwmentioning
confidence: 99%
“…The first point in the width optimization of a single QW was chosen to be 11 monolayers (ML). Indeed, experimental studies of the absorption spectra for single QWs with width of 17 to 260 Å have already demonstrated that, for very narrow wells, the exciton peaks are strongly broadened due to the phonon scattering, and the well width at which the maximum peak absorption is observed is about 35 Å [23].…”
Section: Design Of Cqwmentioning
confidence: 99%
“…This absorption coefficient change is 1.5 times larger than that available from an unstrained MQW structure. 8 Our results can be further improved by increasing QW layers or optimizing the QW structure.…”
Section: Room Temperature Optical Absorption Characteristics Of Gaas/mentioning
confidence: 82%
“…Using the data of Jelley et al [9] for GaAs/AlGaAs MQW's the absorption change Aa in the intrinsic layers will amount to about 7000cm-' (or even more for smaller well width) instead of 2500cm-' for the Franz-Keldysh absorption. Also the ratio of absorption between high and low field can be increased.…”
Section: Field-induced Nonlinear Absorption In N-i-p-i Structuresmentioning
confidence: 97%